Karakterisasi Morfo-Agronomi Dua Galur Harapan Melon Tipe Net (Cucumis melo L.) di Bogor Indonesia - Nadia Mustika Dewi; Zahratul Millah; Sulastri Isminingsih; Widia Eka Putri; Danu Sabda Maulana; Azis Natawijaya (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Melon (Cucumis melo L.) is a high-value horticultural commodity with increasing market demand, but its productivity is constrained by the limited availability of superior varieties and a dependence on imported seeds. This study evaluated the morphological and agronomic characteristics of two net-type melon lines, Fitotech 2 and Fitotech 3, compared with commercial varieties Alina and Amanda. The research was conducted in Cikarawang Village, Bogor, from October 2024 to January 2025, employing a single-factor Randomized Complete Block Design (RCBD) comprising four treatments with three replications each, with 180 plants observed.. Data were collected based on qualitative and quantitative traits, then analyzed using Analysis of Variance (ANOVA), followed by the Honestly Significant Difference (HSD) test at the 5% significance level. Cluster analysis was performed using the average linkage method and Euclidean distance with Minitab software version 22.2.0. The results showed that Fitotech 2 has the highest sugar content (13.78°Brix), a powerful net pattern, uniform round fruit shape, ideal fruit size, and attractive fruit color. Fitotech 3 has the largest stem diameter (0.89 cm), high sugar content (13.44°Brix), optimal flesh thickness (3.09 cm), bright orange flesh color, a powerful net pattern, and a round fruit shape that aligns with market preferences.